Pengaruh Harga Dan Segmentasi Pasar Terhadap Penjualan Hasil Laut Pada PT. Yasuriang Samudera Rezeki - Agus Vianus; Agus Rahmadsyah; Lokot Muda Harahap (Outline Publisher, 2022)
This study aims to determine the effect of partially or simultaneously price and market segmentation on the sale of seafood at PT. Yasuriang Samudera Rezeki. The population in this study are customers of PT. Yasuriang Samudera Rezeki for 52 customers. The sampling technique in this study used saturated samples, which amounted to 52 customers. The research method used is the technique of collecting data through questionnaires. The analytical method used to solve problems and prove hypotheses is descriptive analysis, regression analysis. T test results indicate that the price of a positive and significant effect on the sale of marine products at PT. Yasuriang Samudera Rezeki and Market Segmentation has a positive and significant effect on the sale of seafood at PT. Yasuriang Samudera Rezeki. F test results indicate that the price and market segmentation has a positive and significant effect on the sale of seafood at PT. Yasuriang Samudera Rezeki. The coefficient of determination test results (R2) shows that 68% of the Sales variable is influenced by the Price and Market Segmentation variable, while the remaining 32% is influenced by other variables outside of this study such as service quality, distribution channels, and personal selling.